2018
DOI: 10.1017/s1368980018002628
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory index and depression: a meta-analysis

Abstract: ObjectiveThe purpose of the present meta-analysis was to evaluate the association between the inflammatory potential of diet, determined by the dietary inflammatory index (DII®) score, and depression.DesignSystematic review and meta-analysis.SettingA comprehensive literature search was conducted in PubMed, Web of Science and EMBASE databases up to August 2018. All observational studies that examined the association of the DII score with depression/depressive symptoms were included.SubjectsFour prospective coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 38 publications
5
66
1
6
Order By: Relevance
“…Similarly, another meta-analysis investigating a posteriori derived dietary patterns showed that a diet characterized by a high intakes of fruit, vegetables, whole grain, fish, olive oil, low-fat dairy, and antioxidants and low intakes of animal-derived foods was apparently associated with a decreased risk of depression; in contrast, a dietary pattern characterized by a high consumption of red and/or processed meat, refined grains, sweets, high-fat dairy products, butter, potatoes, and high-fat gravy, and low intakes of fruits and vegetables was associated with an increased risk of depression [43]. There also is evidence that a pro-inflammatory diet, as indicated by a higher DII score, may be associated with an increased risk of having depressive symptoms [44]. Regarding cognitive disorders, a systematic review exploring their relation with various dietary patterns showed that the Mediterranean diet had the strongest evidence supporting protection against cognitive decline among older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another meta-analysis investigating a posteriori derived dietary patterns showed that a diet characterized by a high intakes of fruit, vegetables, whole grain, fish, olive oil, low-fat dairy, and antioxidants and low intakes of animal-derived foods was apparently associated with a decreased risk of depression; in contrast, a dietary pattern characterized by a high consumption of red and/or processed meat, refined grains, sweets, high-fat dairy products, butter, potatoes, and high-fat gravy, and low intakes of fruits and vegetables was associated with an increased risk of depression [43]. There also is evidence that a pro-inflammatory diet, as indicated by a higher DII score, may be associated with an increased risk of having depressive symptoms [44]. Regarding cognitive disorders, a systematic review exploring their relation with various dietary patterns showed that the Mediterranean diet had the strongest evidence supporting protection against cognitive decline among older adults.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the NutriNet-Santé study, we have observed that several dietary indexes reflecting nutritional recommendations were prospectively and inversely associated with the risk to develop depressive symptoms [8]. On the opposite, a western dietary pattern or pro-inflammatory diet characterized among other things by more processed foods has been associated with poor mental health [5, 6, 9]. Previous studies that reported associations between these diets and depression considered nutritional characteristics of the diet and interaction within the food matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The relationships between DII and metabolic syndrome, mortality, cancer and cardiovascular diseases (CVDs) have been studied in several countries [20,[25][26][27][28][29][30]. Interest in the relationship between DII score with depression and anxiety worldwide has resulted in three systematic reviews/ metaanalyses [7,[31][32][33]. Our aim in this study was to quantify the possible inflammatory effects of diet on the occurrence of depression and anxiety in Mashhad, a city in northeastern Iran.…”
Section: Introductionmentioning
confidence: 99%